Solve for c 7(c-6)=8(c-7)

Math
7(c-6)=8(c-7)
Simplify 7(c-6).
Tap for more steps…
Apply the distributive property.
7c+7⋅-6=8(c-7)
Multiply 7 by -6.
7c-42=8(c-7)
7c-42=8(c-7)
Simplify 8(c-7).
Tap for more steps…
Apply the distributive property.
7c-42=8c+8⋅-7
Multiply 8 by -7.
7c-42=8c-56
7c-42=8c-56
Move all terms containing c to the left side of the equation.
Tap for more steps…
Subtract 8c from both sides of the equation.
7c-42-8c=-56
Subtract 8c from 7c.
-c-42=-56
-c-42=-56
Move all terms not containing c to the right side of the equation.
Tap for more steps…
Add 42 to both sides of the equation.
-c=-56+42
Add -56 and 42.
-c=-14
-c=-14
Multiply each term in -c=-14 by -1
Tap for more steps…
Multiply each term in -c=-14 by -1.
(-c)⋅-1=(-14)⋅-1
Multiply (-c)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1c=(-14)⋅-1
Multiply c by 1.
c=(-14)⋅-1
c=(-14)⋅-1
Multiply -14 by -1.
c=14
c=14
Solve for c 7(c-6)=8(c-7)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top